Estudio de factibilidad para la creación de una empresa productora de cajas de cartón corrugado en el departamento de Boyacá (2021)
In Boyacá there are several companies that are dedicated to the distribution of different types of products, from this activity the idea arises of preparing a feasibility study for the creation of a company that is dedicated to the production and marketing of corrugated cardboard boxes in the Boyacá department with headquarters in the city of Tunja.